Analysis of determinant factors of life expectation age in East Nusa Tenggara Province - Nalle, Frederic; Diana Pangastuti, Margareta; Utami, Yohana R.S.S.S. Budi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
East Nusa Tenggara Province is one of the poorest provinces in Indonesia and various prevention programs are being intensified. The conditions of poverty experienced also have an impact on life expectancy. Recognizing this condition, the main objective to be achieved in this study is to determine the effect of the variable Education, Health services and GRDP on the Life Expectancy of the people in the Province of NTT. The analytical tool used is Panel Data Regression Analysis using secondary data published by the Central Statistics Agency during 2014-2018. Time series data was taken for an observation period of 5 years starting from 2014-2018 for the independent variables which include education, health facilities, and gross regional domestic product on the dependent variable life expectancy. So that from a total of 22 regencies/cities in the province of NTT multiplied by 5 years of observation, the number of units of analysis is 110 arithmetical series. The results showed that the variables of Education, Health services and GRDP either partially or simultaneously have a significant effect on life expectancy in East Nusa Tenggara Province.